Nucleobases in molecular recognition: molecular adducts of adenine and cytosine with COOH functional groups - Perumal, Sathiamurthi; Suresh, E.; Pedireddi, V. R. (Angewandte Chemie International Edition, 2005)
Keywords: carboxylic acids; hydrogen bonds; molecular recognition; nucleobases; supramolecular chemistry

Pyridine mediated supramolecular assemblies of 3,5-dinitro substituted benzoic acid, benzamide and benzonitrile - Arora, KK; PrakashaReddy, J; Pedireddi, VR (Tetrahedron, 2005)
Synthesis and characterization of molecular assemblies of pyridine adducts, la, 2a and 3a, of 3,5-dinitrobenzoic acid, 1, 3,5-dinitrobenzamide, 2 and 3,5-dinitrobenzonitrile, 3, respectively, have been reported. All these adducts were obtained by crystallization of 1, 2 and 3 from pyridine. However, crystallization of I from pyridine in the presence of benzene resulted in the formation of a pyridinium adduct, 1b, along with a water molecule. All the adducts crystallize in a 1: 1 molecular ratio except la, which forms a 1:2 adduct, as characterized by single crystal X-ray diffraction method. The adducts crystallize in different space groups-la, orthorhombic, Pna2(1); 1b, monoclinic, P2(1); 2a, monoclinc, C2/c; 3a, triclinic, P-1. In two-dimensional arrangement, la, 1b and 3a form sheet structures. In la, within the two-dimensional sheets, large cavities are formed, which are occupied by pyridine molecules. In 1b, the sheets are catenated to form a chicken-wire network. However, 2a formed a crossed ribbon packing pattern with empty channels in the three-dimensional structure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 3; 5-dinitrobenzamide; 5-dinitrobenzoic acid; 5-dinitrobenzonitrile; channel structures; host-guest complexes; layered structures; molecular recognition; Pyridine

pK(a)-Directed host-guest assemblies: rational analysis of molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine with various aliphatic dicarboxylic acids - Delori, Amit; Suresh, Eringathodi; Pedireddi, V. R. (Chemistry-A European Journal, 2008)
Molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine (1) have been prepared with various aliphatic dicarboxylic acids. The molecular complexes (1a-1i) thus formed by co-crystallizing 1 with oxalic, malonic, succinic, fumaric, acetylene dicarboxylic, glutaric, thiodiglycolic, diglycolic, and adipic acids have been found to give two types of host-guest assemblies that have voids or channels in a three-dimensional arrangement. The different types of host-guest arrangement appear to result from differences in the acidity of the dicarboxylic acids, that is, acids with pK(a) < 3.0 give host networks that consist of 1 and the corresponding acid with water or solvent molecules of crystallization present as guests, whereas acids with pK(a) > 3.0 exist as guests in voids in a host network formed by 1. The former arrangement is observed in adducts 1a, 1b, 1c, and 1h and the latter arrangement is found in adducts 1c, 1d, 1f, 1g and 1i.
Keywords: dicarboxylic acids; host-guest systems; hydrogen bonds; molecular recognition; supramolecular chemistry

Effect of substituent of roof shape amines on the molecular recognition of optically active acids by NMR spectroscopy - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (ChemistrySelect, 2020)
Optically active roof shape derivatives of benzyl amines were synthesized and screened as chiral solvating agents for the study of molecular recognition of chiral compounds by NMR and UV spectroscopy. The effect of substituents on the aromatic ring of benzyl unit is investigated to assess the binding ability with the analyte and an experimental correlation is observed. Altering the substituents on the ring of benzyl amine and the acidic substrates, significantly influence the CSA interactions. The supramolecular interactions between acid and amine in the single crystal X-ray analysis of the diastereomeric salts provide further insight of the mode of molecular recognition.
Keywords: Chiral Solvating Agents; molecular recognition; NMR spectroscopy; Roof Shape Amine; UV spectroscopy

Polymer nanorings with uranium specific clefts for selective recovery of uranium from acidic effluents via reductive adsorption - Kushwaha, Shilpi; Mane, Manoj; Ravindranathan, Sapna; Das, Amitava (ACS Sensors, 2020)
Nanostructured polymeric materials, functionalized with an appropriate receptor, have opened up newer possibilities for designing a reagent that shows analyte-specific recognition and efficient scavenging of an analyte that has either a detrimental influence on human physiology and environment or on its recovery for further value addition. Higher active surface area, morphological diversity, synthetic tunability for desired surface functionalization, and the ease of regeneration of a nanostructured material for further use have provided such materials with a distinct edge over conventional reagents. The use of a biodegradable polymeric backbone has an added significance owing to the recent concern over the impact of polymers on the environment. Functionalization of biodegradable sodium alginate with AENA (6.85% grafting) as the receptor functionality led to a unique open framework nanoring (NNRG) morphology with a favorable spatial orientation for specific recognition and efficient binding to uranyl ions (U) in an aqueous medium over a varied pH range. Nanoring morphology was confirmed by transmission electron microscopy and atomic force microscopy images. The nanoscale design maximizes the surface area for the molecular scavenger. A combination of all these features along with the reversible binding phenomenon has made NNRG a superior reagent for specific, efficient uptake of UO22+ species from an acidic (pH 3-4) solution and compares better than all existing UO22+-scavengers reported till date. This could be utilized for the recovery of uranyl species from a synthetic acidic effluent of the nuclear power. The results of the U uptake experiments reveal a maximum adsorption capacity of 268 mg of U per g of NNRG in a synthetic nuclear effluent. X-ray photoelectron spectroscopy studies revealed a reductive complexation process and stabilization of U(IV)-species in adsorbed uranium species (U@NNRG).
Keywords: biodegradable polymeric backbone; molecular recognition; nanostructured material; sodium alginate; uranium; uranyl-specific receptor